Metaphor Approach In Architecture Design: In Search Of Its Implementation Keywords - Sarvina Fitri Rizky (KBK Peracangan Arsitektur dan Kota Program Studi Arsitektur Fakultas Pendidikan Teknologi, 2022)
This Architecture field has been brought to the era of post-modern. The awareness of reviving the tradition and cultural value has been lifted ever since. As one of architecture style of post-modern, metaphor architecture is too too configure certain thing as the design characteristics. But there were argues as what to be applied, i.e is it solely concrete things what metaphor means and how is it to be valid to be called a metaphor. The effort to create metaphor in design is somehow challenged by the judgement of “copying” and “nonsense”. In this regard, the need of metaphor study appeared strongly. Thus, this current study aims to bring the understanding of metaphor in design by doing deep analyzing. This study followed qualitative methods where the data related metaphor is collected and inducted from literature sources. To mention the focus of study: methods and values of metaphor implementation. Authors conducted a practice designing an institute as another method used in gaining a better overview of applying metaphor. The data were analyzed and presented in narrative and digital drawing. The study showed that metaphor could be in form both of intangible forms (values) and tangible forms, and the value it holds is somehow related to: the way of life, tradition among community, and the creation of cultural object.